1994
DOI: 10.1177/154193129403801583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Older and Younger Driver Responses to Emergency Driving Events

Abstract: Elizabeth Alicandri -Federal Highway AdministrationThis study investigated the responses of older and younger drivers during performance of emergency maneuvers in an interactive driving simulator. Thirty-six drivers, equally distributed among three age groups (20-29; 35-44; 65-74) participated in the 20 miIe simulated drive, during which they encountered four emergency events. Two baseline segments were also collected. The emergency events were situations where other vehicles performed unexpected maneuvers : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Despite their more cautious behavior, older drivers are nevertheless more likely to be killed in a traffic crash than younger drivers and are particularly at risk when attempting to turn across multiple lanes of traffic on higher speed roads. More than half of all crashes involving older motorists are angle crashes, a crash type associated with a driver being struck by an oncoming vehicle when attempting a left turn or a U-turn at a driveway or intersection (Abdel-Aty, Chen, and Radwan 1999;Federal Highway Administration 1995;Hauer 1988;Kloeppel et al 1995;Lyles and Staplin 1991;Maleck and Hummer 1986;Partyka 1983;Preusser et al 1998;Ulfarsson, Kim, and Lentz 2006). The relative risk of involvement in an intersection-related crash increases substantially with age.…”
Section: Crashes Involving Older Motoristsmentioning
confidence: 99%
“…Despite their more cautious behavior, older drivers are nevertheless more likely to be killed in a traffic crash than younger drivers and are particularly at risk when attempting to turn across multiple lanes of traffic on higher speed roads. More than half of all crashes involving older motorists are angle crashes, a crash type associated with a driver being struck by an oncoming vehicle when attempting a left turn or a U-turn at a driveway or intersection (Abdel-Aty, Chen, and Radwan 1999;Federal Highway Administration 1995;Hauer 1988;Kloeppel et al 1995;Lyles and Staplin 1991;Maleck and Hummer 1986;Partyka 1983;Preusser et al 1998;Ulfarsson, Kim, and Lentz 2006). The relative risk of involvement in an intersection-related crash increases substantially with age.…”
Section: Crashes Involving Older Motoristsmentioning
confidence: 99%
“…Due to the small and sometimes non-existent margin of safety offered in these situations, it seem tenable that dnver distraction agents can have a significant effect on successfully Cumulatively, the results of previous research Proceedings of the Human Factors and Ergonomics Society 46th Annual Meeting --2002 PROCEEDINGS of the HUMAN FACTORS AND ERGONOMICS SOCIETY 46th ANNUAL MEETING --2002 avoiding a potentially catastrophic crash. Little research has examined how drivers respond to emergency events (Adams, Flannagan, & Sivak, 1995; Hancock & de Ridder, 2002;Kloeppel, Peters, James, Fox, & Alicandri, 1995) and how drivers respond to emergency event when distracted. It was hypothesized that as the difficulty level of the visual distraction increased driving performance would decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Intersections create locations where opposing streams of traffic cross, and thus locations where conflicts between roadway users may emerge. Previous research has found that a substantial portion of crashes involving older adults tend to occur at intersections, particularly when older adults attempt to turn left across multiple lanes of traffic (Hauer 1988; Kloeppel et al 1995; Partyka 1983; Preusser et al 1998). This variable is the count of intersections in a block group.…”
Section: Introductionmentioning
confidence: 99%